[Cruz y Ortiz] - Cruz/Ortiz, Arquitectos (2001)
Concurso para el Museo de la Evolución Humana en <Burdeos>.
Keywords: CRUZ, ANTONIO; ORTIZ, ANTONIO; ESPAÑA; MUSEOS; MUSEOS DE CIENCIAS NATURALES; CONCURSOS; PROYECTOS